Percutaneous closure of left ventricular pseudoaneurysm. How would I approach it? - Gerard Martí Aguasca (REC: Interventional Cardiology (English Ed.), 2022)
HOW WOULD I APPROACH IT? Authors present an exceptional case of early formation of 1 ventricular pseudoaneurysm after surgical mitral valve replacement complicated with the rupture of the atrioventricular groove that was repaired surgically. The excellent images provided by the computed tomography scan reveal a large multilobulated irregular pseudoaneurysm with an anatomy eligible for percutaneous treatment. For quite a few years, the closure of pseudoaneurysms has been described in the medical literature as case reports and case series with satisfactory results,1 which is why it is currently considered a therapeutic alternative to surgery. In this case, surgery does not seem like a good option due to the patient’s critical condition, and the technical complexity involved in the repair, which is suggestive of percutaneous closure through occluder device implantation. The images provided reveal characteristics associated with location and morphology favorable to the use of percutaneous treatment: saccular morphology of the pseudoaneurysm, circular neck, and relatively small size (< 10 mm), apparently demarcated borders (muscular) in the defect, and distance from mitral annulus without the possibility of a compromised prosthetic function. The excellent images provided by the computed tomography scan allow us to plan the procedure and select the type and size of the device that...